THE IMPACT OF TRAINING AND EXPERIENCE ON THE WORK PERFORMANCE OF CRIMINAL INVESTIGATION UNIT WEST PASAMAN POLICE STATION MEMBERS - Endang Tirtana Putra; Citra Suci Mantauv; Reni Romauli; Nailal Husna (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
ABSTRACT The goals of this research are to (1) determine and analyze the impact that Training has on the Work Performance of Members; (2) determine and analyze the impact that Work Experience has on the Work Performance of Members; and (3) determine and analyze the impact that both Training and Work Experience have on Work Performance of Members. The sample for this research project included 37 people who filled out the survey. This type of research is an example of associative research, which aims to determine the relationship between one or more variables and how one variable affects other factors. Specifically, this type of study examines how one variable impacts others. Both descriptive analysis and multiple linear regression are applied in this particular instance as methodologies for data analysis. It can be seen from the findings of the research that has been carried out that: (1) Training has a positive effect with a t-test value of 2,217 and is significant on Member work performance with a significant value of 0.033 (0.05); (2) Work Experience has a positive effect with a t-test value (2,380) and significant on Member work performance with a significant value of 0.023 (0.05); and (3) There is a positive and significant influence of Training and Work Experience on Member work performance.Keywords: Training, work experience, job performance